E-commerce Teaching Trends in Higher Education: A Meta-synthesis (1999-2023) - Haniva, Respita; Mulyadi, Hari (FKIP Universitas Lampung, 2024)
Abstract: E-commerce Reaching Trends in Higher Education: A Meta-synthesis (1999-2023). The purpose of this study was to review the development of the scientific literature on teaching e-commerce in higher education. The method used was a meta-synthesis of the Scopus database and resulted in 123 relevant articles. The main results of this study are: (1) the scientific literature on teaching e-commerce in higher education began to emerge in 1999; (2) the authors, journals, citations, and countries involved in research in this area are still very few; (3) research collaborations have not been formed significantly; and (4) the common themes of research articles on teaching e-commerce in higher education. The results of this study will be useful for readers to find out the model of writing about e-commerce teaching in higher education, identify potential collaborations with authors and institutions in different countries, and develop new topics on e-commerce in business education and entrepreneurship. Keywords: e-commerce, e-commerce education, business education, entrepreneurship education, bibliometrics.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202431